PENGARUH PENGANGGURAN, INVESTASI, DAN IPM TERHADAP KEMISKINAN DI 34 PROVINSI INDONESIA - Sari, Puji Permata; Ekaputri, Retno Agustina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024DO - 10.24843/EEB.2024.v13.i12.p06, 2024)
Poverty alleviation is the first goal to be achieved in the 17 sustainable development goals. The problem of poverty in Indonesia has always been a government priority that must be resolved. The aim of this research is to examine the influence of poverty, investment and HDI on poverty in 34 provinces of Indonesia. The data used is secondary data in the form of panel data with a period of 5 years in 34 provinces so that the sample used is 170. Meanwhile, the analysis technique used is panel data regression. The results of this research show that there is a significant influence between poverty, investment and HDI on poverty. Meanwhile, individually, it shows that poverty does not influence poverty, and investment and HDI influence poverty negatively and significantly in Indonesia.